PENGARUH MODAL SOSIAL TERHADAP MOTIVASI BERWIRAUSAHA KELOMPOK PENGRAJIN ANYAMAN TALI STRAPPING TUNAS HARAPAN KECAMATAN TUALANG KABUPATEN SIAK - Hasna Ihza Ardianti; Daeng Ayub Natuna; Said Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The formulation of the problem in this study is how high the entrepreneurial motivation and social capital of the group of woven strapping craftsmen of Tunas Harapan, Tualang District, Siak Regency. most likely the influence of social capital on the entrepreneurial motivation of the group of craftsmen of woven strapping ropes in Tunas Harapan, Tualang District, Siak Regency. The purpose of this study was to determine the level of entrepreneurship motivation and social capital of the tunas Harapan woven strapping craftsman group, Tualang District and to determine the effect of social capital on the entrepreneurial motivation of the Tunas Harapan woven strapping craftsman group, Tualang District, Siak Regency. This type of research is ex-post facto, that is, the type of research in which the independent variable is an event that has already occurred. The approach in this study is quantitative, namely research in which the data obtained are related to numbers that lead to the use of statistical analysis techniques. The number of samples in this study were 41 people. The results of this study indicate that there is an influence of social capital on the entrepreneurial motivation of the tunas Harapan strapping rope craftsman group, Tualang District, Siak Regency, so that there is a significant influence between the social capital variable (X) on entrepreneurial motivation (Y) the Tunas Harapan strapping rope craftsman group, Tualang Regency. siak. The influence of weaving craftsmen in Tualang District, Siak Regency is 38.10% with a low interpretation, because 61.90% is still determined by other factors that are not part of this study.Key Words: Social Capital, Entrepreneurial Motivation, Weaving Craftsmen